Soil erodibility in Sangarus Catchment area: Linking soil properties to land degradation and sustainable management strategies - Siregar, Diyanti Isnani; Kusumandari, Ambar; Permadi, Dwiko Budi; Santosa, Sigit Heru Murti Budi (Journal of Degraded and Mining Lands Management, 2026)
Land degradation resulting from agricultural expansion is a significant issue in the Sangarus Catchment area of Lampung, Indonesia, particularly in the upstream region. The conversion of forests into intensive agricultural land has led to declines in soil physical properties and increases in erosion rates. This study aimed to analyze the magnitude of soil erodibility (K-factor) and to evaluate its relationship with soil physical properties, to inform targeted management strategies. The research employed a Land Mapping Unit (LMU) approach, collecting 47 soil samples across the catchment based on soil type, slope, and land cover overlays. The soil samples underwent laboratory analysis for texture, structure, organic matter, and permeability. The K-factor was calculated following the Wischmeier and Smith equation. The results indicated that soil erodibility values (K) in the Sangarus Catchment area ranged from 0.01 to 0.33, with the highest erodibility observed in the upstream area, particularly within mixed dryland agriculture land use. In contrast, secondary forests exhibited the lowest soil erodibility. Statistical analysis revealed that soil permeability was the most significant factor influencing erodibility, followed by other soil properties. These findings suggest that mitigation strategies for the upstream mixed dryland agriculture zones should prioritize Nature-Based Solutions (NBS). Combining agroforestry systems with the intensive application of organic amendments is recommended as a primary strategy. These approaches are essential for improving soil permeability and maintaining organo-mineral complexes, thereby restoring hydrological functions and ensuring the sustainability of the catchment against the risks of degradation.